Communication Making Connections - Seiler, William J.; Beall, Melissa L.; Mazer, Joseph P. (Pearson, 2017)
Communication: Making Connections helps readers make connections in their daily lives, communicate more effectively, and succeed in our ever-changing world. Authors William Seiler, Melissa Beall, and Joseph Mazer balance a thorough-yet straightforward-explanation of basic principles with a solid theoretical foundation, backed by the most up-to-date research. The Tenth Edition has been revised to ensure it is fresher, more useful, and more engaging than previous editions. Relevant examples, thought-provoking questions, and signature boxed features enhance the learning experience and guide readers in mastering their objectives.